Background and episodic breathlessness in advanced cancer patients followed at home. (2nd January 2017) - Mercadante, Sebastiano; Fusco, Flavio; Caruselli, Amanda; Cartoni, Claudio; Masedu, Francesco; Valenti, Marco; Aielli, Federica
Abstract: Background: The aim of this study was to assess the phenomenon of episodic breathlessness in advanced cancer patients followed by palliative care services at home. Methods: A consecutive sample of patients with advanced cancer, admitted to home care for a period of six months, was surveyed. The presence of background breathlessness and episodic breathlessness, their intensity, and drugs used for their treatment were collected. Factors inducing episodic breathlessness, and its influence on daily activities were investigated. Results: Three hundred forty-seven advanced cancer patients admitted to home palliative care were surveyed. The prevalence of breathlessness was 35.3%. The mean intensity of breathlessness was 3.8 (SD 1.96), out of a maximum score of 10 for worst imaginable. Sixty patients (49.2%) were receiving drugs for background breathlessness. In the multivariate analysis the risk of breathlessness increased with cardiovascular disease, chronic obstructive pulmonary disease, and lung cancer while it decreased in patients with a better performance status. The prevalence of episodic breathlessness in patients with background breathlessness was 79.5% and its mean intensity was 7.1 (SD 1.5, range 2–10). The mean duration of episodic breathlessness was 28.6 minutes (SD 47.1, range 1–300 minutes). Forty-three patients (44.3%) were receiving one or more drugs as needed. The majority of episodic breathlessness events were triggered by activity. Episodic breathlessness was interfering with daily activities in 65 patients (67%). Episodic breathlessness wasn't associated with any variable taken into consideration. Conclusion: This study showed that episodic breathlessness frequently occurs in advanced cancer patients admitted to home care, is severe in intensity, is triggered in most cases by activity, and is characterized by a short duration which requires rapid measures.